EVALUASI INVESTASI PERKEBUNAN KELAPA SAWIT POLA PIR DI DESA GADING SARI KECAMATAN TAPUNG KABUPATEN KAMPAR - Hutabarat, Sakti (SOROT, 2011)
Increasig price of Fresh Fruit Bunch and high profit in palm oil platation business has triggedpeople interest in investing and implementing this business. This condition, in turn, hascaused increasing palm oil plantation area. The objective of this research is to evaluateinvestment performance in Nucleus Estate Smallhoders palm oil plantation in Gading Sarivillage, Tapung District, Kampar Regency. This study analyse investment performance of theNES by calculating NPV and IRR criteria and using primary and secondary data. The resultsof this study shows that, with the value of NPV Rp 53.404.339 and IRR 561%, the NESbusiness is profitable and prospectus.